ARRANGEMENT OF ACCESS THROUGH AGRARIAN REFORM FOR INCREASING COMMUNITY INCOME - Westi Utami; M Nazir Salim; R Deden Dani Saleh (HERMENEUTIKA : Jurnal Ilmu Hukum, 2022)
Agrarian reform (RA) as a national strategic program aims to encourage the creation of sources of prosperity and community welfare. This study aims to describe agrarian reform through access arrangement schemes and map out the roles of stakeholders involved in the RA program in Purworejo. The research method was carried out qualitatively, data obtained through interviews with key respondents and through document studies. The results of the study show that in Purworejo Regency, the Agrarian Reform Task Force (GTRA) has prepared a form of RA through strengthening access including optimizing land certificates, especially for Etawa goat breeders and coffee farmers to access capital. In addition, efforts to strengthen community capacity through community empowerment include assistance for Etawa goat breeders and coffee farmers in order to increase their productivity. To support the success of the program, several strategies are needed, including optimizing the role of stakeholders, namely the Office of Cooperatives, Small and Medium Enterprises and Trade, the Office of Settlement and Spatial Planning, the Office of Community and Village Empowerment and related agencies to provide support for program activities and budgets. The role of community leaders as community movers also plays an important role in realizing the success of the Agararia Reform in Purworejo.